Matrine, a potential c-Myc inhibitor, suppresses ribosome biogenesis and nucleotide metabolism in myeloid leukemia - Zhong, Wang-Jing; Ma, Lingdi; Yang, Fanfan; Cao, Jialin; Tan, Junyu; Li, Bohong (Frontiers in Pharmacology, 2022)
Previous studies have shown that matrine, a natural compound extracted from the herb Sophora flavescens, has a good anti-leukemia effect, but its key target and mechanism remains unclear. Here, we found that only c-Myc could respond rapidly to matrine treatment in three myeloid leukemia cell lines, and matrine inhibited both transcription and translation of c-Myc. Ribosome biogenesis and nucleotide metabolism, the key downstream of c-Myc, were were significantly suppressed after matrine treatment. Therefore, our results confirmed that matrine is a special c-Myc inhibitor which suppresses ribosome biogenesis and nucleotide metabolism by inhibiting c-Myc in myeloid leukemia. This study provides scientific basis for the development of matrine derivatives to c-Myc-driven cancers.